Efficiency of Dexamethasone for Treatment of Vasogenic Edema in Brain Metastasis Patients: A Radiographic Approach - Schroeder, Tanja; Bittrich, Paul; Noebel, Clara; Kuhne, Jan Felix; Schroeder, Julian; Schoen, Gerhard; Fiehler, Jens; Kniep, Helge C.; Gellißen, Susanne (Frontiers in Oncology, 2019)
Background and Purpose: Imaging studies quantifying the amount of vasogenic edema reduction (VE) in patients with brain metastases (BM) treated with glucocorticoids (GC) included very limited patient numbers and showed ambiguous results. Here, we aim to determine the radiological effect of GC on VE in BM patients in a large cohort with multiple primary tumor entities in a cross-sectional approach. Materials and Methods: This monocentric retrospective study includes 299 patients first-ever diagnosed with 2759 intra-axial BM on the respective MRI. 126/299 patients received GC prior to MRI due to mass effect of edema on cranial CT scan and clinical symptoms (GC-pos) and 173 patients did not (GC-neg). GC dose was documented in 85/126 patients. All BM and their respective VE were semi-manually segmented on post-contrast T1-weighted images. Results: VE volumes were higher in GC-pos compared to GC-neg (p=0.009) and did not correlate with GC dose. Multivariate linear regression analysis with interaction terms on the assumption that BM volume and BM number influence the probability of GC administration shows that large and higher numbers of BM under GC treatment generate less VE than without (p<0.001 and p=0.038, respectively). The primary tumor type and total BM volume did not influence VE volume. Conclusion: Use of GC is especially effective for treatment of peritumoral edema volumes in cases of larger and multiple BM regardless of primary tumor type and dosage.